Nursing Care in Cultural Birth: Integrative Review - Suarez Maximo, Juan Daniel (2025)
Objective: To analyze the scientific evidence on nursing care in culturally competent childbirth. Method: An integrative literature review was conducted using the PRISMA methodology. The search was carried out in six databases: SCOPUS, PubMed Central, Web of Science, EBSCOhost, Biblioteca Virtual en Salud, and MDPI, between February and May 2024. DeCS descriptors in Spanish, English, and Portuguese were used: Care, Nursing, Childbirth, and Culturally Competent Healthcare, combined using the Boolean operator AND. Specific inclusion and exclusion criteria were applied, ultimately selecting 11 articles. Main results: The included studies reveal that nursing care in childbirth can significantly benefit from the integration of a cultural approach. Humanized practices, partial recognition of traditional medicine, language barriers, and limited training in interculturality were identified. Although staff are reported to be willing to incorporate cultural practices, there are structural, educational, and attitudinal limitations toward traditional midwives. Intercultural care improves maternal satisfaction, reduces the use of unnecessary cesarean sections, and promotes more respectful practices. Overall conclusion: Nursing presents a fundamental pillar of improving its practice through a culturally competent approach. Adopting strategies that integrate women's values, beliefs, and traditions during childbirth allows for more holistic, humane, and respectful care, with direct benefits for the woman and her family.